2016
DOI: 10.3832/ifor1810-009
|View full text |Cite
|
Sign up to set email alerts
|

Thinning effects on soil and microbial respiration in a coppice-originated Carpinus betulus L. stand in Turkey

Abstract: . However, there were no significant differences in either the second year or the 2-year study period. In the thinned plots during the research period, RS was linearly correlated with GC, Ts and FRB. Thinning treatments did not affect RSM, but interestingly, they did affect RFFM, which was greater in the control plots than in the thinned plots. RSM had a significant and positive correlation with soil N and soil pH, while R FFM was linearly correlated with FFC and C/N ratio of the forest floor in both thinned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
1
9
1
1
Order By: Relevance
“…However, Kim et al (2009) reported that the SOC concentration in a 0 to 50 cm soil layer was minimally affected by thinning in a red pine (Pinus densiflora) stand after a one-year treatment. Akburak and Makineci (2016) also showed that thinning had no significant effect on SOC concentration in a coppice-originated European hornbeam (Carpinus betulus L.) stand in Turkey over a two year period. The increase of SOC after thinning during the short term may be explained by an increase in decomposition rates of forest floor.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, Kim et al (2009) reported that the SOC concentration in a 0 to 50 cm soil layer was minimally affected by thinning in a red pine (Pinus densiflora) stand after a one-year treatment. Akburak and Makineci (2016) also showed that thinning had no significant effect on SOC concentration in a coppice-originated European hornbeam (Carpinus betulus L.) stand in Turkey over a two year period. The increase of SOC after thinning during the short term may be explained by an increase in decomposition rates of forest floor.…”
Section: Discussionmentioning
confidence: 96%
“…Understanding the dynamics of SOC fractions and soil properties are more important when evaluating the effect of thinning on carbon pool stability and soil fertility. Furthermore, previous studies on soil labile carbon fractions have mainly focused on microbial biomass (Chen et al, 2015;Akburak and Makineci, 2016), while other SOC fractions based on physical and chemical methods were less studied. Therefore, further study on the variations of SOC fractions and soil microbial diversity in response to shortterm and long-term thinning is needed.…”
Section: Discussionmentioning
confidence: 99%
“…These practices have been implemented in Alabama's Bankhead National Forest (BNF), to mitigate the negative impacts of pest and disease outbreaks (Nobles et al, 2009), reduce fuel loads and accumulated ground flora on forest floors to promote growth of new forage and plants (Converse et al, 2006), increase forest productivity and enhance plant and animal diversity (Ganzlin et al, 2016). Forest productivities, plant nutrient concentrations, microbial richness, enzymatic metabolisms are possibly altered after fire events and forest thinning practices (Wic-Baena et al, 2013;Akburak & Makineci, 2015). Studies have reported an increase (Bååth et al, 1995;Klopatek et al, 1988) and/or decrease (Baar et al, 1999;Grogan et al, 2000), in short-lived bacteria proliferation and little or no increase in soil fungi (Jonsson et al, 1999) due to prescribed burning and/or tree thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Forest functions, nutrient cycling, and chemical and biological properties of soils are altered after a fire event or thinning (Wic‐Baena et al. , Akburak and Makineci ). Successful restoration and regeneration of a forest ecosystem's structure and functions highly depend on the efficacy of nutrient cycling, and carbon is one of the elements involved in the cycles.…”
Section: Introductionmentioning
confidence: 99%